ANALISIS CURAH HUJAN UNTUK PENDUGAAN DEBIT PUNCAK DENGAN METODE RASIONAL (Studi Kasus di Kawasan Hulu DAS Bengawan Solo, Jawa Tengah) - , ROFYAN ANDRIANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rainfall is the most important input component in the hydrologic process. Some of rainfall characteristics, are rainfall intensity (I), duration (t), depth (d) and frequency. Data used in this research comprised of rainfall, land use data and catchment area. The data of rainfall used were daily rainfall in Temon and Wuryantoro. In the research, daily rainfall depth was calculated using frequency analysis, which was started by determining the daily maximum mean rainfall. The daily maximum mean rainfall was used in calculating the statistical parameter to choose the best distribution in Temon and Wuryantoro catchment. Intensity could be calculated by Mononobe method based on return period 2 years, 5 years, 10 years, 20 years and 50 years. The result found in Temon and Wuryantoro was the Normal distribution. Multiplication among runoff coeficient, rainfall intensity and the area of watershed were used to obtain peak discharge with the rational method. Result indicated tahat the peak discharge in Temon watershed for the return periods of 2 years, 5 years, 10 years, 20 years and 50 years were 125,262 m3/second, 150,963 m3/second, 164,426 m3/second, 175,440 m3/second, 187,985 m3/second, respectively. For Wuryantoro watershed were 60,886 m3/second, 78,189 m3/second, 87,209 m3/second, 94,588 m3/second, 102,993 m3/second, respectively.